ВАРИАТИВНОСТЬ ПРЕДСТАВЛЕНИЙ О ВЕЖЛИВОМ РЕЧЕВОМ ПОВЕДЕНИИ ЖЕНЩИН В ЯЗЫКОВОМ СОЗНАНИИ НОСИТЕЛЕЙ РУССКОГО ЯЗЫКА (Филолошки студии, 2019)
Variability of gender stereotypes of the speech behavior existing in language awareness is caused by social parameters of native speakers. By results of research it appeared that in language awareness of each of the social groups investigated in work united on factors "gender", "age", "specialty" and "education", there is "option" or "interpretation" of stereotype about polite speech behavior of women. Allocated in result of the analysis of experimental data signs of speech behavior of women reflect specifics of the maintenance of gender stereotypes of speech behavior for Russian language awareness which consists not so much in the set of these signs, but in their unique, particular combination for Russian lingvoculture, in their quantitative correlation, in their assessment given by carriers of this lingvoculture – by representatives of various social groups. Research of social conditionality of a stereotype of polite speech behavior of women showed, thus, need of complex studying of gender stereotypes for language awareness and impossibility of their consideration for a separation from all contexts of social human life.